Evaluación del control interno en los supermercados multisa y martha corrales en el cantón Latacunga provincia de Cotopaxi” evaluación del control interno en los supermercados multisa y martha corrales en el cantón Latacunga provincia de Cotopaxi - Calo Toapanta, María Abigail (2017)
This project research was developed in Multisa and Martha Corrales Supermarkets in located in Canton Latacunga Province of Cotopaxi, its main purpose is to improve the internal control evaluation so that all activities comply with an adequate process and with the necessary tools through From interviews to managers and internal control questionnaires to accountants and managers of Supermarkets departments.The productivity of the employees and in each one of the activities that are realized was obtained information about the procedures of all the areas that apply within the supermarkets so that they contribute and to fulfill the proposed objective, in addition the results will be of way effective for the development of the same so that all information is reliable, the project benefited Multisa Supermarkets, Martha Corrales employees who are part of them as well as society that is in its environment due to the evolution of production ends In an economic evolution it foments sources of employment, improvement of benefits for its employees and a monetary circulation that benefits the country in itself. When developing the internal control evaluation it was evidenced that the great majority of the processes were not adequate and if an internal control is not carried out it will lead to an economic affectation for the owners, for which in this project the new controls were implemented in each one of activities in all departments of supermarkets indicated, Socially it will contribute in the improvement of remunerations, timely payment to the workers.